Potential Complications of Percutaneous Vertebroplasty Combined with Interstitial Implantation of 125I Seeds for Metastatic Spinal Tumors: A Case Report and Literary Review. (28th August 2019) - Xie, Lunli; Yan, Zhenlin; Zhu, Jun; Chen, Xudong; Yang, Changyuan; Su, Xing; Quan, Keqin; Pu, Dan
Abstract : Percutaneous vertebroplasty is often used to acquire the stability of the spine and relieve the pain caused by osteoporotic vertebral compressive fracture (OVCF). 125 I seeds have been used for application of local therapy for tumors. A combined treatment was reported in previous literatures. Thus, this case report is aimed at reporting a patient with an occurrence of delayed radioactive myelopathy, who accepted percutaneous vertebroplasty combined with interstitial implantation of 125 I seeds for metastatic spinal tumors, and at reviewing the published literatures.